Forum for Institutional Thought: A platform for an exchange of ideas about institutional economics in Poland - Jurczuk, Anna; Śliwa, Renata; Łapniewska, Zofia; Zachorowska-Mazurkiewicz, Anna (Social Entrepreneurship Review, 2023)
This article presents the history, objectives, and scope of activity of the Forum for Institutional Thought Association. The Forum is an initiative by a group of social sciences’ representatives gathered around the belief that the institutional approach currently offers the best way to understand the world, particularly the changes that happen in the economies undergoing a systemic transition.